Informed Consent in Pringsewu Regional General Hospital: Legal Evidence Perspective - Samino, Samino; Perdana, Agung Aji; Kuntoro, Selamet (Universitas Aisyah Pringsewu, 2022)
Quality health care is the right of every patient and his family. One of the indicators of quality services is the fulfillment of informed consent in accordance with the laws and regulations. Preliminary studies of several informed consent documents at Pringsewu Hospital found that all of them were not filled out completely. This study aims to analyze informed consent documents from the perspective of legal evidence.The study was conducted at Pringsewu Hospital in July 2021. The research method used a qualitative descriptive analysis approach, with 75 informed consent documents and two informants. How to collect data by reviewing the informed consent document that has been filled in at the hospital medical record installation, by checking the completeness of filling out the informed consent document for the five most types of actions, and in-depth interviews with the responsible leadership.The results showed that 75 informed consent documents were reviewed, none of which were filled out completely. The five most important indicators were not filled in completely, consecutively: name and signature of witness II, name and signature of witness I, gender of the patient, and gender of the giver of consent. To improve the completeness of filling out documents, the hospital will provide education to doctors, nurses, and administrative staff, as well as strict supervision. It was concluded that incomplete informed consent documents, as legal evidence, were low quality. The hospital leaders should conduct socialization to doctors, nurses and administrative staff regarding the importance of filling out the medical treatment approval form properly and completely.Abstrak: Pelayanan kesehatan bermutu merupakan hak setiap pasien dan keluarganya. Salah satu indikator pelayanan bermutu terpenuhinya pelaksanaan informed consent sesuai peraturan perundang-undangan. Studi pendahuluanterhadap beberapa dokumen informed consent di RSUD Pringsewu ditemukan semuanya tidak terisi dengan lengkap. Penelitian bertujuan untuk menganalisis dokumen informed consent perspektifalat bukti hukum.Penelitian dilakukan di RSUD Pringsewu Juli 2021. Metode penelitian menggunakan pendekatan analisis deskriptif kualitatif, dengan 75 dokumen informed consent dan dua informan. Cara pengambilan data dengan mengkaji dokumen informed consent yang telah isi di instalasi rekam medik RS, dengan melakukan checklist kelengkapan pengisian dokumen informed consent pada lima jenis tindakan terbanyak, dan wawancara mendalam pihak pimpinan yang bertanggung jawab.Hasil penelitian menunjukkan 75 dokumen informed consent yang dikaji tidak ada satupun dokumen yang terisi dengan lengkap. Lima indikator terbanyak tidak diisi dengan lengkap berturut-turut: nama dan tanda tangan saksi II, nama dan tanda tangan saksi I, jenis kelamin pasien, dan jenis kelamin pemberi persetujuan. Untuk meningkatkan kelengkapan pengisisan dokumen RS akan melakukan edukasi terhadap para dokter, perawat, dan tenaga administrasi, serta pengawasan secara ketat. Disimpulkan dokumen informed consent yang tidak terisi dengan lengkap, sebagai alat bukti hukum kualitasnya rendah. Pimpinan RS melakukan sosialisasi pada para dokter, perawat dan tenaga administrasi mengenai pentingnya pengisian formulir persetujuan tindakan kedokteran dengan baik dan lengkap.